TENSION BETWEEN SCHOOLS OF THOUGHT: ASWAJA AND WAHABI IN ACEH - Firdaus M. Yunus; M. Hasbi Amiruddin (Islam Futura, 2021)
Religious life in Aceh has received attention from various parties when Aswaja and Wahabi start preaching on religious rituals. Aswaja accuses the teaching of Wahhabism is against the Islamic values and Aqidah adopted by the people in Aceh. The Acehnese who embraces Aswaja must strictly reject the teachings of Wahabi followers. Aswaja's accusations were highly opposed by Wahabi groups that later led to tensions and pressures on both sides. This research is a qualitative research with data collection methods carried out through observation, documentation, and interviews with selected informants. The results obtained from the study include first, Aswaja, the only religious group, began to be disturbed with the emergence of Wahhabism in several places. Second, Wahhabism preaching movement that was once carried out clandestinely is now carried out openly in several mosques in Aceh. Third, there is a tension in convincing the truth of the schools of thought.